Examining religiosity to determine student ethical behavior intention - Nurdian Susilowati; Ida Nur Aeni; Angga Pandu Wijaya (International Journal of Evaluation and Research in Education (IJERE), 2022)
Religiosity remains a black box in educational research; only a few studies conducted regarding religiosity. Therefore, this study was conducted to examine some variables on students’ religiosity. This article attempts to determine the influence of attitude, injunctive norm, moral norm, and perceived behavioral control on student's ethical behavioral intention through religiosity. There were 273 education students from several higher education in Indonesia participated in this study. Questionnaire was used to collect data, while path analysis was used to analyze the data. The results found that injunctive norm, perceived behavioral control, and religiosity directly affected the intention of ethical behavioral. Besides, there was no direct effect between attitude and moral norms and the intention of ethical behavioral. Then, religiosity competent to become the intervening variable of attitude, injunctive norm, moral norm, perceived behavioral control on ethical behavioral intention. The paper can explain the black box that found attitude of a student was influenced by their religiosity or faith and belief. Other than attitude and moral norms, the stronger the religiosity could help students to create a good behavior.